A decisão judicial idealmente fundada - Rodrigo Cândido Rodrigues (2022)
What should be the ideal reasoning of a judicial decision remains a question still unanswered. Brazilian law establishes that any judicial decision shall be grounded on reasoning, but it fails to establish what would be the ideal reasoning. This ideal, however, can be understood and identified, from a logical-normative point of view, if analyzed through the universal pure logical structures of Husserl’s transcendental idealism, which explore knowledge by distinguishing between empty meanings and filled meanings, as well as the structure of founded and founding parts, in the constitution of categorical objects, such as the judicial decision. Through the knowledge of these structures, it is possible to understand what is the normative ideal of the reasoning grounding a judicial decision, and to distinguish an ideally grounded judicial decision from one that does not meet this ideal.